PELAKSANAAN ASAS ITIKAD BAIK DALAM PERJANJIAN KERJASAMA USAHA XAFA GROUP KEBAB TURKI ALA FANDAWA DI KOTA PEKANBARU - MALELA, GITA REGINA; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The cooperation agreement between the owner of capital and the manager of venture capital of Xafa Group Kebab Turki Ala Fandawa is a legally-made agreement to act as a law for the parties making it, in accordance with the principle of "pacta sunt servanda" agreement law. In the present development, the principle of pakta sunt servanda is based on the principle of good faith. Thus, the cooperation agreement between the owner of capital and the manager of venture capital of Xafa Group Kebab Turki Ala Fandawa must also be carried out in good faith as set forth in Article 1338 Paragraph (3) of the Civil Code which states that: "An agreement must be executed in good faith". The purpose of writing this thesis, namely: First, find out whether the implementation of cooperation agreements Xafa Group Kebab Turki Ala Fandawa has been implemented in accordance with the principle of good faith. Secondly, to know the problems and constraints that occurred during the implementation of the cooperation agreement of Xafa Group Kebab Turki Ala Fandawa business in Pekanbaru city.This type of research can be classified in the type of juridical empirical research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problems studied. The research was conducted at the House of Production Xafa Group Kebab Turki Ala Fandawa. The nature of descriptive research with primary data sources, secondary data and tertiary data, while the population and sample are the parties in the cooperation agreement examined in this study. Data collection techniques are interviews and literature review.From the results of research problems there are two main things that can be concluded. First, the implementation of the cooperation agreement of Xafa Group Kebab Turki Ala Fandawa business is not in accordance with the principle of good faith. Because the business capital manager has violated the contents of the agreement on the term of the agreement and decides in advance the cooperation agreement without any deliberation between the parties. The Manager in this case has violated Article 8 Paragraph (1) cooperation agreement and Article 1338 Paragraph (3) Civil Code. Second, the constraining factors encountered in the implementation of the business cooperation agreement are: rare communication between the parties and sales revenue that often do not reach the target. Authors' suggestion: firstly, the parties should be open and explain the relevant information in the agreement and be expected to understand the contents of the agreed agreement so that no party will be harmed. Secondly, it is necessary to have good communication between the parties because the cooperation will not run smoothly without any communication and good faith from the parties because the cooperation agreement is not only to gain profit for one party but for all related parties.Keywords : Agreement-Cooperation-Good faith